KEABSAHAN HASIL CETAK (SCREENSHOT) SEBAGAI ALAT BUKTI ELEKTRONIKi DALAMiPEMERIKSAAN PERKARA PERDATA - Tyah Safira (Gapenas Publisher, 2022)
The development of computer technology, telecommunications, and information has gone so far that today is very different from 10 years ago with trade and industrial business has given rise to transaction models because of the advances and advantages of technology. In today's digital age computers, telecommunications, and information have proliferated enormously, making the utilization of the technology drive screenshot proving to be one of the tools of evidence used in the trial. The study aims to know the legali arrangement ofi the evidentiali printing (screenshots) i in thei civil casei hearing, andi to learni the strengthi of thei printingi evidencei (screenshot) i in thei civil suiti proving. The researchi method usedi was a normative-lawi study withi a constitutionali approach associatedi with it. Researchi shows thati the legali setting ofi screenshot evidencei can be usedi in civili suit trials. Then, i the strengthi of thei screenshot toolsi had ai bindingi proof forcei for bothi the judgei and the parties. Thus, i it may bei concluded thati a screenshot evidencei device couldi be usedi in a civili hearing becausei it was ini the samei positioni as thei other evidencei and couldi be usedi legally, i and thisi screenshot evidencei was binding oni both judgei and othersi who wouldi use it